Literature Review : Prevalensi Jumlah Leukosit Pada Sampel Urine Pasien dengan Pemasangan Kateter - Putri, Pipit Sagita; Aini, Aini; Mentari, Ika Nurfajri; Pauzan, Pauzan (JSN : Jurnal Sains Natural, 2025)
The use of urinary catheters is very common in hospitals. Urinary catheters are the most common cause of bacteriuria. Urinary tract infections are the cause of more than 1/3 of all hospital-acquired infections. Most of these infections (at least 80%) are caused by invasive procedures or urinary tract instrumentation, usually in the form of catheterization. Urine sediment examination aims to detect and identify insoluble materials in urine. The purpose of this study was to determine the prevalence of leukocyte counts in patients with catheter placement based on a literature review and to analyze the number of leukocytes in patients with catheter users based on a literature review. The method used was Systematic Literature Review (SLR). The results of this study obtained the results of the number of samples based on gender in women as many as 223 people and in men 147 people, with a total number of patients as many as 370. then the results of the number of samples based on patient age, the number of patients who were most catheterized at the age of 56-65 as many as 101 patients (27.0%), followed by age 46-55 as many as 96 patients (25.0%), age 36-45 as many as 68 patients (18.0%), age 26-35 as many as 39 patients (10.0%), age 17-25 as many as 30 patients (8.0%), and age> 65 as many as 36 patients (9.0%) with a total of 370 patients. The results of the study can be concluded that catheter installation can cause urinary tract infections.